PENGARUH LATIHAN FARTLEK TERHADAP DAYA TAHAN PADA TIM BOLA BASKET SMA NEGERI 8 PEKANBARU - Nazrun Efendi; Kristi Agust; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The problem in this research is the low endurance of the Pekanbaru 8 Public High School basketball team. This can be seen in the games in quarters 1 and 2, the athletes played very well, but during the 3rd and 4th quarters, the level of play decreased, so that the points were left behind so that they experienced defeat. The aim of this study was to determine the effect of fartlek training on the endurance of the basketball team. The population in this study were all basketball athletes at SMA Negeri 8 Pekanbaru using a total sampling technique of 12 athletes. This type of study uses Pre-test Post Test design, the instrument used in this study is Bleep test using data analysis of normality test and t-test. Based on the statistical analysis of the t-test, the difference value is 3.14, yielding a tcount of 12.076 and a ttable of 1.796. Means tcount > ttable. It can be concluded that fartlek training (X) affects endurance (Y) in the men's basketball team at SMA Negeri 8 Pekanbaru.Key Words: Basketball, Endurance, Fartlek Training